Identification and Characterization of Chemical Constituents from Ammopiptanthus nanus Stem and Their Metabolites in Rats by UHPLC-Q-TOF-MS/MS - Chen, Guanru; Sun, Yanpei; Yushan, Dilnur; Shaerbayi, Nuerjiamali; Zhang, Hongjuan; He, Hongliang; Jin, Yang; Chen, Lina (Planta Medica, 2023)
Ammopiptanthus nanus as a Kirgiz medicine is widely used for the treatment of frostbite and chronic rheumatoid arthritis. However, due to a lack of systematic research on the chemical components of A. nanus and their metabolites, the bioactive components in it remain unclear. Herein, a reliable strategy based on UHPLC-Q-TOF-MS/MS was established to comprehensively analyze the chemical components and their metabolites in vivo. In total, 59 compounds were identified from A. nanus stem extract, among which 14 isoflavones, 10 isoprenylated isoflavones, 4 polyhydroxy flavonoids, 9 alkaloids and 1 polyol were characterized for the first time. After oral administration of A. nanus stem extract, 30 prototype constituents and 28 metabolites (12 phase I and 16 phase II metabolites) were speculated on and identified in rat serum, urine and feces. Furthermore, the metabolic pathways of the chemical components were systematically analyzed and proposed. In conclusion, the chemical components from A. nanus stem and their metabolites in vivo were first studied, which may provide useful chemical information for further study on the effective material basis and pharmacological mechanism of A. nanus.
Keywords: Ammopiptanthus nanus; Leguminosae; Kirgiz medicine; chemical components; metabolic pathways; UHPLC-Q-TOF-MS/MS